1620a How to promote health and work ability of firefighters using computer-based assessment method of physical work capacity. (24th April 2018) - Lusa, S; Punakallio, A; Halonen, J; Wikström, M
Abstract : Introduction: According to the Finnish regulations the health and physical work capacity of operative firefighters has to meet the demands of work throughout their career, therefore they must be evaluated regularly. This study is part of large research and developmental project of the assessment, feedback and follow-up method of firefighters' physical work capacity (FireFit method). Methods: The aim was to find out short term effectiveness of the use of FireFit method. Web-based questionnaire was sent to 18 actors of all 22 regional rescue services (RRS) and to their occupational health personnel (OHP). The response rate was 60%. In addition, the actors of two RRS and their OHP were interviewed about the developmental needs of the method especially concerning ageing firefighters. Result: The quality, equality and the use of tests in professional manner has improved. They reported that it has been easier to influence the problems of work ability using the system. As a whole, the comprehensive and work related feedback from the assessments has made discussion easier leading to the real causes of the problems and to wider health promotion issues. The consultation of OHP has been more prevalent and early enough, especially for persons with musculoskeletal problems. A total of 77% of the respondents felt that the quality and comprehensiveness of physical training has improved. However, there were also developmental needs. For example, in all RRS there should be an established and well-known action plan for what to do when ageing firefighter fails to pass the cut-off values of the tests. Discussion: The FireFit method seems to act as a tool of co-operation between OHP and actors in RRS. It seems to make early interventions more appropriate for firefighters with decreasing work ability. High quality use of the method requires continuous education and training of its users.